Interactions Between Limb and Environmental Mechanics Influence Stretch Reflex Sensitivity in the Human Arm - Krutky, Matthew A. (American Physiological Society, 2010)
Stretch reflexes contribute to arm impedance and longer-latency stretch reflexes exhibit increased sensitivity during interactions with compliant or unstable environments. This increased sensitivity is consistent with a regulation of arm impedance to compensate for decreased stability of the environment, but the specificity of this modulation has yet to be investigated. Many tasks, such as tool use, compromise arm stability along specific directions, and stretch reflexes tuned to those directions could present an efficient mechanism for regulating arm impedance in a task-appropriate manner. To be effective, such tuning should adapt not only to the mechanical properties of the environment but to those properties in relation to the arm, which also has directionally specific mechanical properties. The purpose of this study was to investigate the specificity of stretch reflex modulation during interactions with mechanical environments that challenge arm stability. The tested environments were unstable, having the characteristics of a negative stiffness spring. These were either aligned or orthogonal to the direction of maximal endpoint stiffness for each subject. Our results demonstrate preferential increases in reflexes, elicited within 50–100 ms of perturbation onset, to perturbations applied specifically along the direction of the destabilizing environments. This increase occurred only when the magnitude of the environmental instability exceeded endpoint stiffness along the same direction. These results are consistent with task-specific reflex modulation tuned to the mechanical properties of the environment relative to those of the human arm. They demonstrate a highly adaptable, involuntary mechanism that may be used to modulate limb impedance along specific directions.